Demokrasi untuk Indonesia : pemikiran politik Bung Hatta - Suleman, Zulfikri, 1959- (Jakarta : Penerbit Buku Kompas, 2010)
Thoughts of Mohammad Hatta on democracy.
'April 2010.'
Includes bibliographical references (p. 257-265) and index.
Keywords: Hatta, Mohammad, -- 1902-1980.; Democracy